Probiotics Supplementation and Performance of Broiler Rabbits - Sharma, K. Geetanjali; Vidyarthi, V. K.; Zuyie, R. (Indian Journal of Animal Nutrition, 2018)
The experiment was conducted to investigate the effect of different levels of probiotics on performance of Soviet Chinchilla rabbits. For this, 15 growing rabbits (7 weeks old) were randomly distributed into 3 treatment groups consisting of 5 animals in each group. The rabbits in control group (T1) were fed with broiler finisher ration. The rabbits of the other two groups were also provided the same broiler finisher diet as in T1 group along with probiotics at a level of 2.5 g (T2) and 5.0 g (T3) per kg feed. The average live weight of the rabbit was similar (mean 2.16 kg) while gain in live weight was higher (P<0.05) in group T2 (0.211 kg). The lowest feed intake (3.79 kg/rabbit) with better (P<0.05) feed conversion ratio (2.63) was also observed in group T2. The performance index (180.11), carcass weight, cost of production per kg rabbit and the net profit per kg rabbit (` 75.36) was better (P<0.05) in group T2 as compared to other groups. It could be concluded that supplementation of probiotics @ 2.5 g/kg feed showed better performance of the rabbits in terms of live weight, gain in body weight, FCR and profit per unit of production.